Research on Improved Integration Sliding Mode Controller of PMSM - ZHOU Yang; SHEN Zhan; HU Yao-hua (机车电传动)
Based on the mathematical model of permanent magnet synchronous motor, id=0 and the phase space vector pulse widthmodulation were introduced to control the motor. For the requirements of the high-performance servo system, an integral sliding modecontroller was proposed to improve the gain of the switching control integral segment. Simulation results based on MATLAB/SIMULINKshowed that the proposed system had smaller overshoot, faster response, little chattering and stronger robustness by compared to traditionalintegral sliding mode control.